Interaction of Cutibacterium acnes with human bone marrow derived mesenchymal stem cells: a step toward understanding bone implant- associated infection development. (1st March 2020) - Dubus, M.; Varin, J.; Papa, S.; Rammal, H.; Chevrier, J.; Maisonneuve, E.; Mauprivez, C.; Mongaret, C.; Gangloff, S.C.; Reffuveille, F.; Kerdjoudj, H.
Abstract: Crosstalk between mesenchymal stem cells (MSCs) and bacteria plays an important role in regulating the regenerative capacities of MSCs, fighting infections, modulating immune responses and maintaining tissue homeostasis. Commensal Cutibacterium acnes ( C. acnes) bacterium becomes an opportunistic pathogen causing implant-associated infections. Herein, we examined MSCs/ C. acnes interaction and analysed the subsequent bacteria and MSCs behaviours following infection. Human bone marrow derived MSCs were infected by two clinical and one laboratory C. acnes strains. Following 3h of interaction, all bacterial strains were able to invade MSCs. Viable intracellular bacteria acquired virulence factors by increasing biofilm formation and/or by affecting macrophage phagocytosis. Although the direct and indirect (through neutrophil stimulation) antibacterial effects of the MSCs secretome were not enhanced following C. acnes infection, ELISA analysis revealed that C. acnes clinical strains are able to license MSCs to become immunosuppressive cell- like by increasing the secretion of IL-6, IL-8, PGE-2, VEGF, TGF-β and HGF. Overall, these results showed a direct impact of C. acnes on bone marrow derived MSCs, providing new insights into the development of C. acnes during implant-associated infections. Statement of significance: The originality of this work relies on the study of relationship between human bone marrow derived mesenchymal stem cells (MSCs) phenotype and C. acnes clinical strains virulence following cell infection. Our major results showed that C. acnes are able to invade MSCs, inducing a transition of commensal to an opportunistic pathogen behaviour. Although the direct and indirect antibacterial effects were not enhanced following C. acnes infection, secretome analysis revealed that C. acnes clinical strains were able to license MSCs to become immunosuppressive and anti-fibrotic cell- like . These results showed a direct impact of C. acnes on bone marrow derived MSCs, providing new insights into the development of C. acnes during associated implant infections. Graphical abstract: Image, graphical abstract